2023
DOI: 10.1155/2023/9766002
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial, Antioxidant, and in silico NADPH Oxidase Inhibition Studies of Essential Oils of Lavandula dentata against Foodborne Pathogens

Abstract: Food is always subjected to microbial infection and lipid peroxidation, which frequently leads to serious food intoxications. In the present study, essential oils (EOs) extracted from Lavandula dentata Moroccan species and its major component (linalool) were chemically characterized and their antioxidant potential and antibacterial properties against foodborne pathogenic bacteria were examined. EOs phytochemical profile was carried out using gas chromatography-mass spectrometry analysis (GC-MS). The antioxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The Moroccan Phytochemicals Database (MPDB) serves as a comprehensive resource for those interested in exploring the therapeutic potential of Moroccan plant phytochemicals. Research has shown that Moroccan plants offer a wide range of biological activities, including antimicrobial, anticancer, antidiabetic, and cardiovascular effects [ 14 , 15 , 16 , 17 ]. The MPDB provides access to a carefully curated collection of phytochemicals derived from these plants, making it an essential tool for researchers in drug discovery, traditional medicine, and phytochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…The Moroccan Phytochemicals Database (MPDB) serves as a comprehensive resource for those interested in exploring the therapeutic potential of Moroccan plant phytochemicals. Research has shown that Moroccan plants offer a wide range of biological activities, including antimicrobial, anticancer, antidiabetic, and cardiovascular effects [ 14 , 15 , 16 , 17 ]. The MPDB provides access to a carefully curated collection of phytochemicals derived from these plants, making it an essential tool for researchers in drug discovery, traditional medicine, and phytochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…The essential oil was subsequently dried with anhydrous sodium sulfate and then preserved in a refrigerator at 4°C until ready for use. 19…”
Section: Extraction Of Essential Oilmentioning
confidence: 99%
“…A total of 100 µL of each sample was mixed with 2.5 mL of the previously prepared mixture. After incubation in a water bath at 50 • C, the solutions' absorbance was measured at 470 nm at 0 min and after 120 min against a blank without β-carotene [62]. Under the same conditions, distilled water and BHT were also used as controls.…”
Section: β-Carotene Discoloration Assaymentioning
confidence: 99%
“…The microbial strains' sensitivity was tested by the agar well diffusion method frequently used to assess antimicrobial activity [62]. First, 1 mL of fresh microbial culture was added to Petri dishes (90 mm) containing MHA and SB medium.…”
Section: Agar Well Diffusion Assaymentioning
confidence: 99%